Postnatal deletion of podoplanin in lymphatic endothelium results in blood filling of the lymphatic system and impairs dendritic cell migration to lymph nodes - Bianchi, R; Russo, E; Bachmann, S; Proulx, S; Sesartic, M; Smaadahl, N; Watson, S; Buckley, C; Halin, C; Detmar, M (American Heart Association, 2016)
Objective The lymphatic vascular system exerts major physiological functions in the transport of interstitial fluid from peripheral tissues back to the blood circulation and in the trafficking of immune cells to lymph nodes. Previous studies in global constitutive knockout mice for the lymphatic transmembrane molecule podoplanin reported perinatal lethality and a complex phenotype with lung abnormalities, cardiac defects, lymphedema, blood-filled lymphatic vessels and lack of lymph node organization, reflecting the importance of podoplanin expression not only by the lymphatic endothelium, but also by a variety of non-endothelial cell types. Therefore, we aimed to dissect the specific role of podoplanin expressed by adult lymphatic vessels. Approach and Results We generated an inducible, lymphatic-specific podoplanin knockout mouse model (PdpnΔLEC) and induced gene deletion postnatally. PdpnΔLEC mice were viable and their lymphatic vessels appeared morphologically normal with unaltered fluid drainage function. Intriguingly, PdpnΔLEC mice had blood-filled lymph nodes and vessels, most frequently in the neck and axillary region, and displayed a blood-filled thoracic duct, suggestive of retrograde filling of blood from the blood circulation into the lymphatic system. Histological and FACS analyses revealed normal lymph node organization with the presence of erythrocytes within lymph node lymphatic vessels but not surrounding high endothelial venules. Moreover, FITC painting experiments revealed reduced dendritic cell migration to lymph nodes in PdpnΔLEC mice. Conclusions These results reveal an important role of podoplanin expressed by lymphatic vessels in preventing postnatal blood filling of the lymphatic vascular system and in contributing to efficient dendritic cell migration to the lymph nodes.